Weight loss, performance and psychological related states in high-level weightlifters - Durguerian, A.; Bougard, C.; Drogou, C.; Sauvet, F.; Chennaoui, M.; Filaire, E. (International Journal of Sports Medicine, 2016)
We examined the effects of a rapid weight loss on dietary intakes, psychological parameters and physical performance of 11 international weightlifters. During the first period (T1), all subjects maintained their body weight and participated in a simulated weightlifting competition. Then, they were assigned into 2 groups depending on whether they lost (Group 2) or maintained (Group 1) their body weight over 6 days. A battery of tests was performed at T1 and after a 6-day food restriction (T2), including assessment for body composition, performance, evaluation of mood states and fatigue. Dietary data were collected using a 6-day diet record. A 4.34% reduction of body weight was achieved by a significant reduction of total energy intakes (- 40%), inducing a significant alteration of the general recovery score (p<0.05) and evaluated through the Recovery-Stress Questionnaire for Athletes. Increase in conflicts/pressure, emotional stress and physical complaints were observed. Intakes of vitamins B1, B3, B6, B9 and magnesium were significantly lower than the recommendations during the weight loss period. However, the food restriction did not impair weightlifting performance. Reduced energy and micronutrient intakes, inducing a rapid weight loss, could be a limiting factor to training adaptations and a threat towards athlete`s health if frequently used.